2017
DOI: 10.4186/ej.2017.21.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Rotary Friction Welding of Dissimilar Joints between SSM356 and SSM6061 Aluminium Alloys Produced by GISS

Abstract: Abstract. The objective of research to investigate the parameters, microstructure and mechanical properties of butt joint SSM356 with SSM6061 aluminum alloy by using RFW processes. The main parameters such as rotation speeds are 1550, 1700 and 1850 rpm, burn-off length are 2, 2.5 and 3 mm respectively. For experiment found that, both materials have weld ability to get along well though it has a different chemical composition, the changes in welded metals microstructures occurs deformation leads to smaller part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…They concluded that rotational speed produced the maximum effect on the weld strength followed by friction pressure and forging pressure. Chainarong et al [ 15 ] successfully joined SSM356 and SSM6061 aluminum alloys produced by the gas induced semisolid casting technique (GISS) through rotary friction welding. They reported greater strength and microhardness within the weld interface and thermomechanical zone (TMAZ), which was caused due to higher rotary speed and burn-off length.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that rotational speed produced the maximum effect on the weld strength followed by friction pressure and forging pressure. Chainarong et al [ 15 ] successfully joined SSM356 and SSM6061 aluminum alloys produced by the gas induced semisolid casting technique (GISS) through rotary friction welding. They reported greater strength and microhardness within the weld interface and thermomechanical zone (TMAZ), which was caused due to higher rotary speed and burn-off length.…”
Section: Introductionmentioning
confidence: 99%
“…Suppachai Chainarong et al [10] welded the two dissimilar aluminum alloys using friction welding method and found that strength and hardness of the welded joint was higher. The effect of burn off length and rotational speed on the hardness and tensile strength were analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Rotary friction welding (RFW) is a solid-state welding method, where heat is produced by rubbing components together under load. In this process, one of the workpieces is held stationary while the other rotates, making the workpieces surfaces soften and leading them bond together [13]. In RFW there are three phases [14]: i) heat-up stage, ii) burn-off stage, and iii) forging stage.…”
Section: Introductionmentioning
confidence: 99%